Naturalistic Data from Greek-speaking Toddlers Using the LENA Device - Binos, Paris; Taxitari, Loukia (My University, 2023)
The Language Environment Analysis (LENA Research Foundation, Boulder, CO, USA), or LENA system, is a “talk pedometer” combining a wearable audio recorder with automated vocal analysis (LENA Research Foundation, 2014). This first study ever with Greek-speaking families aimed to reveal the trends they follow in their everyday lives concerning various aspects of their linguistic behaviour with their children. Through LENA, parents, teachers and clinicians could easily monitor the amount and quality of their child's language input